1998
DOI: 10.1590/s1516-31801998000400006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of blood pressure in maintenance hemodialysis

Abstract: Context: Seasonal variation in arterial blood pressure has been reported in studies with hypertensive and normotensive subjects. However, the influence of seasonal change on blood pressure of hemodialysis patients has not been reported. Objective: To investigate the seasonal variation of blood pressure in Brazil, a tropical country, in patients on hemodialysis. Design: Prospective, cohort study. Setting: Dialysis unit of a tertiary medical center (a teaching hospital of the University of São Paulo School of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Similar findings for predialysis BP were noted in studies of 16 patients in Brazil (19), 102 patients in Uruguay (20), 53 patients in France (18), 144 patients in Japan (21), and the 1416 patients in this study (Table 1). Plausible mechanisms for the lower BP in the summer include decreased interdialytic fluid gain and thus decreased intravascular volume during that season.…”
Section: Variations In Bpsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings for predialysis BP were noted in studies of 16 patients in Brazil (19), 102 patients in Uruguay (20), 53 patients in France (18), 144 patients in Japan (21), and the 1416 patients in this study (Table 1). Plausible mechanisms for the lower BP in the summer include decreased interdialytic fluid gain and thus decreased intravascular volume during that season.…”
Section: Variations In Bpsupporting
confidence: 90%
“…The magnitudes of the reported seasonal changes were as great as 12 mmHg for systolic pressure and 7 mmHg for diastolic pressure in one study (18). Similar to findings for the general population, BP values for the dialysis patients in three of those studies (18,19,21) were inversely correlated with outdoor temperatures, with the highest mean BP occurring in the winter. In addition, BP was positively correlated with outdoor humidity in two studies (18,21).…”
supporting
confidence: 67%
“…Secondly, blood pressure has a seasonal change from highest in winter to lowest in summer. This seasonal variation coincides with that of stroke [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 61%
“…Higher IDWG and pre-SBP have been observed in winter periods in dialysis patients dwelling in Northern [ 2 , 3 , 5 ] and Southern temperate zones [ 6 ]. To the best of our knowledge only a single study from Brazil addressed seasonal differences in blood pressure in a tropical climate [ 19 ]. This study reported higher diastolic and mean blood pressure in winter, but no difference in IDWG between seasons.…”
Section: Discussionmentioning
confidence: 99%